The world of Manet, 1832-1883 - Schneider, Pierre 1925-; Time-Life Books ([Nederland] Time-Life Books B.V., 1968)
An account of the life, career and paintings of 19th century French artist Edouard Manet, with background information on the time.
The reluctant revolutionary -- A passion for reality -- Painter of the present -- The gang at the Cafe Guerbois -- The flowering of impressionism -- Their subject is Paris -- A painful summation.
Includes bibliographical references (page 186) and index.
Keywords: Manet, Edouard -- 1832-1883.